Europe lagging behind in ICT evolution: Patenting trends of leading ICT companies - Timo Seppälä; Olli Martikainen (The Research Institute of the Finnish Economy (ETLA), 2011)
In this paper, we examine new Internet ecosystem strategies through comprehensive OECD PATSTAT patent data analyses focusing on mobile operating system software firms. We also describe current patent disputes between mobile hardware firms and mobile operating system software firms in the US and their relevant intellectual property in order to highlight the changes and decisions made within current mobile value chains, which may then enable the further examination of strategic decisions of individual firms. Based on OECD PATSTAT and our descriptive analyses, we find that the latest strategic decisions made by the mobile hardware and operating system firms target industry-level competition on intellectual property and control over new industry convergence, whereas the value of hardware-based intellectual property is measured and evaluated against software and heuristics related intellectual property. This industry convergence includes the evolution of new ecosystems based on Apple, Google and Microsoft technologies that will change the role of several firms in the mobile value chain.
Keywords: L86; L8; L25; 330; Apple; Microsoft; Google; Nokia; ICT; ecosystems; intellectual property; patenting; Mobiltelefon; Umwelt; Immaterialgüterrechte; Patent; Europa; USA